Damage potential and phenology of the Colorado potato beetle [Coleoptera: Chrysomelidae] on potato in southern Alberta - Noronha, C.; Duke, G.M.; Goettel, M.S. (Phytoprotection, 2002)
The phenology and damage potential of the Colorado potato beetle (Leptinotarsa decemlineata) were studied in the potato producing area in southern Alberta. Experimental plots were established at Lethbridge in 1998, 1999 and 2000, and at Vauxhall in 1998 and 1999. At each site, one plot was protected against the beetle by application of insecticides while the other was "unprotected." Natural potato beetle populations quickly colonized unprotected plots each year. Overwintered adults appeared in plots by mid June with mean densities reaching between 0.3 and 0.6 per plant. Eggs were laid on young plants with mean densities reaching two egg masses per plant by late June. Maximum larval densities reached 9.5 per plant for each of 1st, 2nd and 3rd instars and 14 per plant for 4th instars. Maximum density for newly emerged adults was 57 per plant in mid-July at the 2000 Lethbridge unprotected plot. Defoliation was very low at the beginning of the season but increased sharply when 3rd and 4th instar populations peaked and continued to rise as new adults emerged. Maximum defoliation occurred at the Lethbridge plot in 2000 with 100% defoliation by 10 August. Total yields in all unprotected plots ranged from 10 to 40% lower than in the protected plots. Mean density of overwintering adults within potato plots was 76 beetles m-2 with a maximum of 232 m-2. Mean overwintering mortality was 22% and mean depth of overwintering adults was 12 cm, with 63% of the beetles collected at depths ≤ 10 cm. Our results indicate that the phenology of the beetle is similar to that reported in areas where population buildups were rapid and devastating soon after insecticide resistant populations appeared. Consequently the beetle must be considered as a serious threat to potato production in southern Alberta.